2020
DOI: 10.3390/nu12102942
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Glycomacropeptide on Food Allergy with Gastrointestinal Manifestations in a Rat Model through Down-Regulation of Type 2 Immune Response

Abstract: Glycomacropeptide (GMP) is a bioactive peptide derived from milk κ-casein with immune-modulatory and anti-inflammatory properties. Food allergy (FA) is an adverse immune reaction with a broad spectrum of manifestations. Allergen intake induces persistent intestinal inflammation and tissue damage. In this study, the anti-allergic activity of GMP was evaluated using a rat ovalbumin (OVA)-induced FA model with gastrointestinal manifestation. Rats were orally GMP treated from 3 days prior and during FA development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 108 publications
(156 reference statements)
0
14
1
Order By: Relevance
“…Elevated presence of MC may be accompanied with enhanced MC activity. The enhancement of proteases levels in food allergy was previously shown [48,57,66]. However, we did not find significant inhibitory effects of resveratrol on mRNA expression of MC proteases in duodenum and colon sections, which have been strongly enhanced in OVAchallenged animals.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…Elevated presence of MC may be accompanied with enhanced MC activity. The enhancement of proteases levels in food allergy was previously shown [48,57,66]. However, we did not find significant inhibitory effects of resveratrol on mRNA expression of MC proteases in duodenum and colon sections, which have been strongly enhanced in OVAchallenged animals.…”
Section: Discussioncontrasting
confidence: 59%
“…Besides infiltration with inflammatory cells into affected tissues, food allergies are further associated with several histological changes in the intestine [48,[55][56][57]. We observed that tissue damage, evaluated as epithelial barrier disruption, was slightly enhanced in intestinal tissues of OVA mice, with no significant attenuation by resveratrol.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…New pharmacological therapies in the management of food allergies aim at regulating inducing cells and suppressing the native and adaptive responses responsible for triggering allergic reactions [65][66][67]. These therapies are not allergen-dependent, acting nonspecifically, which differentiates them from immunotherapy.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%